Penerapan Metode Multi Attribute Utility Theory (MAUT) Dalam Pemilihan Rumah Kost - Sari, Rita Novita; Hayati, Ratna Sri (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
The development of information technology is currently developing rapidly. The use of information technology is very broad in various fields of life. The choice of boarding house is one of the things that is not easy to do. The problem often faced when choosing a boarding house is that boarders find it difficult to get information about boarding houses. Decision support system is a method that helps in making decisions on a particular problem, where no one can make a definite decision. Multi Attribute Utility Theory (MAUT) is a method of decision making. MAUT is a method where looking for weighted sums of the same values in each utility in each attribute. By applying the MAUT method in the selection of boarding houses, it can give good suggestions or recommendations on boarding houses.